El mar: un camino hacia la paz - Valenzuela, Andrés Palma (Studi sulla Formazione/Open Journal of Education, 2014)
On the occasion of the presentation in the city of Florence in June 2013 the book La voce della pace comes dal mare. Experiences cooperazione e ricerca di internazionali per a convivenza tra le culture, and what i dirriti sviloppo a cura di Silvia Guetta, these pages provide an analysis of some of the most significant contributions of Professor Guetta on the Culture of Peace. Specifically, the relationship that Education for Peace offers the interiority of the person and, in particular, to teachers and educators as agents of peace.